1998
DOI: 10.1093/brain/121.10.1895
|View full text |Cite
|
Sign up to set email alerts
|

Induction of experimental autoimmune neuritis with peripheral myelin protein-22

Abstract: Two myelin proteins, P2 basic protein and P0 glycoprotein, can induce experimental autoimmune neuritis (EAN), a model of human inflammatory neuropathy. We investigated whether peripheral nerve myelin protein-22 (PMP22), the gene for which is duplicated in hereditary motor sensory neuropathy type la, can also induce EAN. PMP22 cDNA produced by the reverse transcriptase-polymerase chain reaction from rat sciatic nerve was expressed in Escherichia coli as a fusion protein with glutathione-S-transferase (GST). Ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 38 publications
2
39
0
1
Order By: Relevance
“…Demyelinative changes in both peripheral nerves and spinal nerve roots have also been reported in hypertrophic hereditary motor and sensory neuropathy, 4 protein zero-deficient mice, 9,26 peripheral myelin protein-22 deficient mice, 40 Trembler mice, 2 and Trembler-J mice 13 and in animal models of inflammatory demyelinating neuropathy. 1,14,17,24,38,39 In 2 mice with POEMS, which is a monoclonal plasma cell disorder characterized by polyneuropathy (P), organomegaly (O), endocrinopathy (E), monoclonal gammopathy (M), and skin changes (S), spinal nerve roots and sural nerves showed the same pathologic changes of demyelination, remyelination, and inflammatory cell infiltration, 42,47 and in 3 cases of diabetic neuropathy, there was severe loss of both large and small MF in sural nerves while segmental demyelination and remyelination was the main finding in both dorsal and ventral spinal roots. 32 Distal intramuscular and subcutaneous MF have rarely been examined in demyelinating peripheral neuropathies, although skin biopsy has been used in the diagnosis of disorders involving unmyelinated 21 and myelinated 11,23,25 fiber disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Demyelinative changes in both peripheral nerves and spinal nerve roots have also been reported in hypertrophic hereditary motor and sensory neuropathy, 4 protein zero-deficient mice, 9,26 peripheral myelin protein-22 deficient mice, 40 Trembler mice, 2 and Trembler-J mice 13 and in animal models of inflammatory demyelinating neuropathy. 1,14,17,24,38,39 In 2 mice with POEMS, which is a monoclonal plasma cell disorder characterized by polyneuropathy (P), organomegaly (O), endocrinopathy (E), monoclonal gammopathy (M), and skin changes (S), spinal nerve roots and sural nerves showed the same pathologic changes of demyelination, remyelination, and inflammatory cell infiltration, 42,47 and in 3 cases of diabetic neuropathy, there was severe loss of both large and small MF in sural nerves while segmental demyelination and remyelination was the main finding in both dorsal and ventral spinal roots. 32 Distal intramuscular and subcutaneous MF have rarely been examined in demyelinating peripheral neuropathies, although skin biopsy has been used in the diagnosis of disorders involving unmyelinated 21 and myelinated 11,23,25 fiber disorders.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] We have shown that recombinant, homologous PMP22 induces experimental autoimmune neuritis (EAN) and that these animals develop antibodies against the immunising antigen. 11 We have recently identified anti-PMP22 antibodies in 52% of patients with Guillain-Barré syndrome (GBS) and 35% of those with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). 12 Using a different assay others have detected anti-PMP22 antibodies in 70% of patients with HMSN1a and 60% with HMSN2 as well as in those with other neuropathies.…”
mentioning
confidence: 99%
“…Experimental autoimmune neuritis is an accurate model of the neurophysiological and pathological features of human inflammatory demyelinating polyradiculoneuropathy. It is clearly a primarily T cell mediated disease which can be induced by immunization with P0, P2 and now, PMP22 myelin proteins 26 . Although, each subtype of GBS presumably has a relatively independent immunopathogenesis.…”
Section: Pathogenesismentioning
confidence: 99%